2019
DOI: 10.1530/joe-18-0374
|View full text |Cite
|
Sign up to set email alerts
|

The key role of a glucagon-like peptide-1 receptor agonist in body fat redistribution

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are an ideal therapy for type 2 diabetes and, as of recently, for obesity. In contrast to visceral fat, subcutaneous fat appears to be protective against metabolic diseases. Here, we aimed to explore whether liraglutide, a GLP-1RA, could redistribute body fat via regulating lipid metabolism in different fat depots. After being fed a high-fat diet for 8 weeks, 50 male Wistar and Goto-Kakizaki rats were randomly divided into a normal control group, a diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 52 publications
(63 reference statements)
2
21
0
1
Order By: Relevance
“…Liraglutide has also been shown to reduce total body fat and to increase fat free mass in type 2 diabetes in one study 11 . Based on observations in animals, it is suggested that GLP‐1 receptor agonists increase energy expenditure through increased lipid oxidation and thermogenesis 11,12 . In animals and in morbidly obese patients, GLP‐1 receptor expression has been shown to increase in proportion to the co‐existent insulin resistance 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liraglutide has also been shown to reduce total body fat and to increase fat free mass in type 2 diabetes in one study 11 . Based on observations in animals, it is suggested that GLP‐1 receptor agonists increase energy expenditure through increased lipid oxidation and thermogenesis 11,12 . In animals and in morbidly obese patients, GLP‐1 receptor expression has been shown to increase in proportion to the co‐existent insulin resistance 13 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Based on observations in animals, it is suggested that GLP-1 receptor agonists increase energy expenditure through increased lipid oxidation and thermogenesis. 11,12 In animals and in morbidly obese patients, GLP-1 receptor expression has been shown to increase in proportion to the co-existent insulin resistance. 13 However, there are no previous data on the loss of body fat in association with the preservation of lean body mass following liraglutide in patients with T1DM.…”
Section: Changes In Glucagon Incretins and Meal Responsementioning
confidence: 99%
“…Recently, GLP-1 RAs have been used as a preferred treatment for patients with diabetes and obesity [26,27]. Previous studies have suggested that liraglutide can play a hypoglycemic role by increasing insulin secretion, improving islet cell function and reducing body weight in diabetic mice and obese rats [28][29][30]. Others also con rmed that GLP-1 RAs inhibited the formation of lipid droplets in different cells lines [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that GLP-1 increases the expression of lipolytic markers while reducing expression of lipogenic and adipogenic genes in adipose tissue, with distinct effects on subcutaneous and visceral adipose tissue [40]. In another study, expression of brown adipose tissuerelated genes was upregulated in subcutaneous adipose tissue of rats after treatment with liraglutide [41]. In line, it was recently shown that liraglutide-induced weight reduction resulted in a greater reduction of visceral adipose tissue volume than lifestyle counselling at similar weight reduction [42].…”
Section: Characteristicmentioning
confidence: 90%